2009
DOI: 10.1016/j.taap.2009.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium — A metallohormone?

Abstract: Cadmium is a heavy metal that is often referred to as the metal of the 20th Century. It is widely used in industry principally in galvanizing and electroplating, in batteries, in electrical conductors, in the manufacture of alloys, pigments, and plastics, and in the stabilization of phosphate fertilizers. As a byproduct of smelters, cadmium is a prevalent environmental contaminant. In the general population, exposure to cadmium occurs primarily through dietary sources, cigarette smoking, and, to a lesser degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 81 publications
(86 reference statements)
1
113
1
6
Order By: Relevance
“…Consistent with these results is the hypothesized role of cadmium as a metallohormone [Byrne et al 2009]. Once cadmium enters cells the damage it induces has been attributed primarily to its interference with zincmediated metabolic processes, possibly by molecular mimicry of zinc [Bridges and Zalups 2005].…”
Section: Animal and In Vitro Studiesmentioning
confidence: 61%
“…Consistent with these results is the hypothesized role of cadmium as a metallohormone [Byrne et al 2009]. Once cadmium enters cells the damage it induces has been attributed primarily to its interference with zincmediated metabolic processes, possibly by molecular mimicry of zinc [Bridges and Zalups 2005].…”
Section: Animal and In Vitro Studiesmentioning
confidence: 61%
“…In addition, in Drosophila cells, depletion of hsc70 has been proven to lead to upregulation of hsp27 [23], and therefore the two events could be linked in PLP2 asODN-transfected cells. On the other hand, it is known that hsp27 promoter contains an imperfect but functional estrogen-responsive element and that Cd is a metallo-estrogen, since it binds and activates steroid receptors [24,25]; therefore, PLP2 might be involved in the counteraction of such activating role played by Cd on hsp27 gene. Furthermore, Kindas-Mügge et al [26] demonstrated the decrease of the proliferation rate of hsp27-overexpressing MDA-MB231 cells; thus, it can be hypothesized that PLP2-induced restraining effect on hsp27 expression may be addressed to protect cell growth behavior from the toxic effect of the metal.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium can also act as an endocrine disruptor, and it is carcinogenic. (Järup et al, 1998;Waalkes, 2003; for reviews, see Agency for Toxic Substances & Disease Registry, Toxicological Profile for Cadmium, 2008, http:// www.atsdr.cdc.gov/toxprofiles/tp.asp?idϭ48 &tidϭ15; Byrne et al, 2009;Joseph, 2009).…”
mentioning
confidence: 99%